Guidelines for evaluating school health and family life education in Eastern Caribbean countries - Volume 2: Summative evaluation - Pan American Health Organization. Caribbean Program Coordination (PAHO Office of Caribbean Programme Organization, 1991)
These guidelines were prepared as resource materials to encourage and support efforts by teachers, principals, and education administrators, to evaluate the progress and effectiveness of school health and family life education (HFLE) in the Caribbean. The guidelines therefore sought to: 1) recapture some of the basic purposes and dimensions of evaluation, and 2) provide an expanded selection of strategies, methodologies and instruments. The materials are presented in two volumes: Volume 1 – Formative evaluation and Volume 2 – Summative evaluation.
Prepared under the School Health and Family Life Education Project jointly sponsored by the Carnegie Corporation of New York and the Pan American Health Organization (Office of the Caribbean Program Coordinator) Volume 1 - Formative Evaluation and Volume 2 - Summative Evaluation
Keywords: health and family life education; HFLE